Acquiring a new concept is not explicable-by-content - Shea, N (2011)
Carey's book describes many cases in which children develop new concepts with expressive power that could not be constructed out of their input. How does she side-step Fodor's paradox of radical concept nativism? I suggest that it is by rejecting the tacit assumption that psychology can only explain concept acquisition when it occurs by rational inference or other transitions that are explicable-by-content. © 2011 Cambridge University Press.